The Empirical Analysis to Enhance Taiwanese Satisfaction in Buying Vietnam coffee - Thi Nham Le; Chia Nan Wang; Ying Fang Huang (International Journal of Advances in Applied Sciences, 2017)
Vietnam coffee industry has been well-known over the world for many decades. However, Vietnam products do not meet Taiwan customers’ expectation, it has lead to urgent challenges for the industry. Therefore, the paper proposed the integrated approach by using exploratory factor analysis, reliability analysis and regression analysis. The results of this study were used to formulate and recommend on how to improve the products of Vietnam coffee by using SPSS statistics for analysis. The major findings of this paper was found out that there are six important determinants of Taiwanese decision-making in buying coffee. In order to enhance customer satisfaction with the coffee products from Vietnam, the companies need right strategies to improve these six groups of factors. The paper contributes meaningful and helpful results to the development of Vietnam coffee industry.